(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we discuss the existence of nonoscillatory solutions of first order nonlinear neutral difference equations of the form We use the Knaster-Tarski xed point theorem to obtain some sucient conditions for the existence of nonoscillatory solutions of above equations. Example are given to illustrate the main results.